Long covid and mental and physical health: A cross‐sectional study of adults in California - Tyler B. Mason; Tara K. Knight; Ryan Lee; Shirin E. Herzig; Daniella Meeker; Jason N. Doctor (Public Health Challenges)
Abstract Introduction Most people recover from COVID‐19 infection over a short period of time, but a minority of individuals experience symptoms over a longer duration (≥28 days), termed “long covid.” The purpose of the current study was to examine differences between individuals with a long covid diagnosis (i.e., diagnosed long covid), who believe they do or might have long covid (i.e., self‐reported long covid), and people without long covid. Methods Adults who had been diagnosed with COVID‐19 completed survey questions about COVID‐19 history, long covid, and mental and physical health. Analysis of covariance models showed an effect of long covid group (i.e., diagnosed, self‐reported, and no long covid) with anxiety, depression, physical function, fatigue, social roles/activity limitations, and pain interference. Results Analyses demonstrated that the self‐reported long covid group had significantly greater anxiety and depression than the no long covid group. The diagnosed long covid group had significantly greater physical function problems than the no long covid group. Both diagnosed and self‐reported long covid groups had significantly greater fatigue, social roles/activity limitations, and pain interference as compared to the no long covid group. Conclusion Overall, physical health challenges were reported by individuals with long covid, with fatigue being the most significant symptom. In addition, negative mental health was only experienced by individuals with self‐reported long covid, suggesting the importance of long covid diagnosis and treatment.